Program Kombinasi Intervensi Stimulasi Motorik Oral dalam Meningkatkan Kesiapan Keterampilan Minum Per-Oral pada Bayi Prematur - Sari, Maya; Allenidekania, Allenidekania; Waluyanti, Fajar T (Journal of Telenursing (JOTING), 2024)
This study aims to evaluate the efficacy of integrating multiple oral motor stimulation interventions in facilitating the readiness for oral feeding among premature neonates.. A systematic review methodology was adapted for this inquiry. Extensive literature searches were conducted across prominent databases, including PubMed, EBSCO, Sage Journal, Taylor & Francis, Clinical Key for Nursing, and Proquest. A total of six articles, all randomized controlled trials, were selected and meticulously reviewed. The results of this systematic review indicate that the interventions employed include combinations of oral motor stimulation with supplementary nursing, kinesthetic tactile techniques, non-nutritive sucking (NNS), swallowing exercises, and sensorimotor stimulation. The findings suggest that these interventions are effective in enhancing oral feeding readiness by shortening the transition period to oral feeding and promoting breastfeeding fulfillment. Additionally, they have been shown to increase breastfeeding rates and reduce concurrently the duration of hospitalization. This research provides valuable insight for improving neonatal care and optimizing feeding practices. Keywords: Feeding Readiness, Oral Motor Stimulation, Premature Infants